Urinary phthalate concentrations and mortality risk: a population-based study - Beyer, Anika; Schorgg, Paula; Karavasiloglou, Nena; Sarwar, Sneha; Rohrmann, Sabine; Bärnighausen, Till; Cassidy, Aedin; Connolly, Lisa; Kühn, Tilman (Environmental research, 2022)
Phthalates are widely used as plasticizers. Laboratory-based mechanistic and epidemiological studies suggest that phthalates are detrimental to human health. Here, we present prospective analyses on phthalate exposure and all-cause, as well as cause-specific, mortality from the National Health and Nutrition Examination Survey (NHANES), a population-based cohort.
Gesehen am 13.12.2022